Iranian women and gender in the Iran-Iraq War - Farzaneh, Mateo Mohammad (Gender, culture, and politics in the Middle East., 2021)
"Hundreds of thousands of Iranian women participated in the Iran-Iraq War (1980-88), yet their significant role has gone unnoticed. Using primary sources, Farzaneh both chronicles the ways in which women participated in the conflict and explores the factors that motivated them to do so."